Bond Ratings in Non-Financial Companies Listed on the Indonesian Stock Exchange - Ety Nila Nikmati; Nurjanti Takarini (East Asian Journal of Multidisciplinary Research, 2023)
In order for a company to exist and survive, one of them can be achieved through the company's financing sources. The company in this case requires capital or funds. The need for capital or funds can be financed with own capital in the form of short-term or long-term debt obtained from one of them, namely bonds. This study aims to analyze the effect of leverage, liquidity, profitability and company size on bond ratings of non-financial companies. In this study, using multiple linear regression analysis methods with the SPSS 25 program to process the data. The data used is secondary data which is the annual financial statements of non-financial companies on the Indonesia Stock Exchange in 2019- 2021. The observation data used is 132 data. The results of this study indicate that leverage, liquidity do not contribute to bond ratings, profitability is able to contribute to bond ratings, and company size is able to contribute to bond ratings.